Analisis Kompetensi Pedagogik Guru - Muh. Syata, Wahyu; Sabillah, Bellona Mardatillah; Subur, Hikmayani; Damayanti, Damayanti (Universitas Islam Ahmad dahlan, 2024)
The function of teachers is crucial in accomplishing educational objectives. The role and competence of the teacher determines the student's learning outcome. The main player in learning is the teacher, who drives the transformation of education that produces a lot of change. The use of learning methods and media by teachers keeps students motivated and not bored in learning. The research method used is qualitative descriptive using literature or library study. There are three aspects of pedagogical competence: planning, implementation and evaluation of learning. The learning plan is the most important thing because it includes curriculum study activities, preparing curricula, RPP, learning strategies, learning resources and the atmosphere of learning activities. The use of media technology as a support for the learning process will help teachers in transferring information to students so that teachers can build active interaction with students. Teachers are able to help and ensure students are actively involved and create learning goals achieved. Learning evaluation is intended to examine various practical strategies for better further learning. Then good pedagogical competence is the success of teaching and learning